2014
DOI: 10.1097/scs.0000000000000373
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic Analysis of Msx1 and Msx2 Involved in Craniofacial Development

Abstract: Msx1 and Msx2 were revealed to be candidate genes for some craniofacial deformities, such as cleft lip with/without cleft palate (CL/P) and craniosynostosis. Many other genes were demonstrated to have a cross-talk with MSX genes in causing these defects. However, there is no systematic evaluation for these MSX gene-related factors. In this study, we performed systematic bioinformatic analysis for MSX genes by combining using GeneDecks, DAVID, and STRING database, and the results showed that there were numerous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 36 publications
0
15
0
3
Order By: Relevance
“…These findings clearly guide us to perform further functional studies in the future treatment. [ 9 ] In our findings, a female patient had an exceedingly rare combination with achondroplasia and multiple-suture CS. Despite these specific features of achondroplasia, synostosis of the metopic, coronal, lambdoid, and squamosal sutures was found.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…These findings clearly guide us to perform further functional studies in the future treatment. [ 9 ] In our findings, a female patient had an exceedingly rare combination with achondroplasia and multiple-suture CS. Despite these specific features of achondroplasia, synostosis of the metopic, coronal, lambdoid, and squamosal sutures was found.…”
Section: Introductionmentioning
confidence: 58%
“…However, there is no systematic evaluation for these MSX gene-related factors. [ 9 ] In bioinformatic analysis for MSX genes by combining GeneDecks, DAVID, and STRING database, results showed that there were numerous genes related to MSX1, MSX2, M-TWIST, T-TWIST genes, IRF6, TP63, Dlx2, Dlx5, Pax3, Pax9, Bmp4, Tgf-beta2, and Tgf-beta3 that have been demonstrated to be involved in CL/P. FGFR2, FGFR1, FGFR3, and TWIST1 that were involved in CS.…”
Section: Introductionmentioning
confidence: 99%
“…Their blood supplies also differ (Vandevska-Radunovic et al 1994). During the growth and development of the jaw, the maxilla and mandible are differentially expressed for certain genes; DLX1/DLX2 mainly regulates the development of the maxilla, whereas MSX1 and GSC mainly regulate the development of the mandible (Somma et al 2011, Dai et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study related to craniofacial development, network analysis of two genes MSX1 and MSX2 revealed several other genes of interest [ 6 ]. MSX1 and MSX2 were found to be related to IRF6, TP63, DLX2, DLX5, PAX3, PAX9, BMP4, TAB2, and TAB3.…”
Section: Resultsmentioning
confidence: 99%
“…Such analyses were made possible by the availability of curated protein-protein interaction (PPI) databases such as STRING [ 1 ], MINT [ 2 ], BioGRID [ 3 ], HPRD [ 4 ] and DIP [ 5 ]. Network analysis using previously published PPI data has been carried out extensively, some examples of which are the study of craniofacial development [ 6 ], Hutchinson-Gilford progeria syndrome [ 7 ], glioblastoma [ 8 ] and general drug discovery [ 9 ]. Recognizing the capability of network based studies, there have been focused efforts to determine disease specific interactomes using high-throughput technology such as yeast 2-hybrid (Y2H) and to annotate proteins and even make inferences about functions and relations to new diseases.…”
Section: Introductionmentioning
confidence: 99%